Water content of 27 sediment cores collected at 15 stations in the western Barents Sea during cruise JR16006 (July-August 2017) as part of the Changing Arctic Ocean programme. - Faust, Johan C; Maerz, Christian (British Oceanographic Data Centre, National Oceanography Centre, NERC, UK, 2020)
In July - August 2017, 27 sediment cores were collected using a multi-corer at 15 stations along a general south-north gradient in the western Barents Sea during the cruise JR16006. Sediment cores were sliced and frozen immediately after recovery and were later analysed for water content. The sediment cores were collected for the Changing Arctic Ocean project Changing Arctic Ocean Seafloor (ChAOS).